Study of the relation between kVp and X-ray tube output of general X-ray machine at Hua Hin Hospital, Prachuap Khiri Khan - Chawee Bunkloy (Journal of Associated Medical Sciences, 2017)
Introduction: X-rays are used to diagnose abnormalities in body. However, during radiographs patients will receive radiation doses. As X-ray machine has different quantities and quality of X-rays, it is therefore important for radiological technologists to set radiation doses for particular patients.